2003
DOI: 10.1094/mpmi.2003.16.5.398
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Involvement of Defense Signaling Pathways in Components of the Nonhost Resistance of Arabidopsis thaliana to Rust Fungi Also Reveals a Model System for Studying Rust Fungal Compatibility

Abstract: Seventeen accessions of Arabidopsis thaliana inoculated with the cowpea rust fungus Uromyces vignae exhibited a variety of expressions of nonhost resistance, although infection hypha growth typically ceased before the formation of the first haustorium, except in Ws-0. Compared with wild-type plants, there was no increased fungal growth in ndr1 or eds1 mutants defective in two of the signal cascades regulated by the major class of Arabidopsis host resistance genes. However, in the Col-0 background, infection hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
80
3
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 25 publications
3
80
3
2
Order By: Relevance
“…However, there may exist a mechanistic connection between H 2 O 2 accumulation in the cytoplasm of the invaded cells due to structural perturbation of the EHC (and papillae) and upregulation of SA signaling. Subcellular callosic structures similar to the EHC have long been observed in other host-pathogen interactions (Heath and Heath, 1971;Bushnell, 1972;Donofrio and Delaney, 2001;Mellersh and Heath, 2003;Soylu et al, 2003), suggesting that EHC formation may be a general basal defense mechanism against haustorial invasion and a target for suppression by the pathogens for pathogenesis. Based on the correlation between RPW8.2 expression and H 2 O 2 accumulation in the HC along with EHC formation, one can envision an exquisite postinvasion defense mechanism in Arabidopsis that involves targeting RPW8.2 to the host-pathogen interface to enhance H 2 O 2 accumulation and EHC formation for constraining the haustorium while protecting the host cell itself.…”
Section: Two Functions Of Rpw82 Both Contribute To Resistancementioning
confidence: 94%
“…However, there may exist a mechanistic connection between H 2 O 2 accumulation in the cytoplasm of the invaded cells due to structural perturbation of the EHC (and papillae) and upregulation of SA signaling. Subcellular callosic structures similar to the EHC have long been observed in other host-pathogen interactions (Heath and Heath, 1971;Bushnell, 1972;Donofrio and Delaney, 2001;Mellersh and Heath, 2003;Soylu et al, 2003), suggesting that EHC formation may be a general basal defense mechanism against haustorial invasion and a target for suppression by the pathogens for pathogenesis. Based on the correlation between RPW8.2 expression and H 2 O 2 accumulation in the HC along with EHC formation, one can envision an exquisite postinvasion defense mechanism in Arabidopsis that involves targeting RPW8.2 to the host-pathogen interface to enhance H 2 O 2 accumulation and EHC formation for constraining the haustorium while protecting the host cell itself.…”
Section: Two Functions Of Rpw82 Both Contribute To Resistancementioning
confidence: 94%
“…Although until recently little was known about the biochemical defenses that contribute to nonhost resistance, cytological descriptions suggested that a majority of inappropriate fungal pathogens were unable to breach the plant cell wall and infiltrate host cells (Yun et al, 2003;Zimmerli et al, 2004). However, some variation in penetration efficiency exists among different host and fungal pathogen combinations (Mellersh and Heath, 2003). These studies also showed that plants respond actively to attack by inappropriate pathogens and do not rely solely on preformed and constitutive barriers for protection against inappropriate pathogens (Meyer and Heath, 1988;Zimmerli et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These studies also showed that plants respond actively to attack by inappropriate pathogens and do not rely solely on preformed and constitutive barriers for protection against inappropriate pathogens (Meyer and Heath, 1988;Zimmerli et al, 2004). Furthermore, it appears that operationally, nonhost resistance can be divided into penetration resistance, barriers limiting entry of the pathogen into cells, and postpenetration resistance, mechanisms that act intracellularly if penetration resistance is overcome (Fernandez and Heath, 1991;Huitema et al, 2003;Mellersh and Heath, 2003;Yun et al, 2003;Zimmerli et al, 2004;Lipka et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preformed defence mechanisms include formation of plant cytoskeleton and barriers against pathogenic invasion (Kobayashi et al 1997;Yun et al 2003), and constitutive accumulation of a variety of secondary metabolites, especially those with antimicrobial activity (Osbourn 1996). Induced defence mechanisms comprise of accumulation of components involved in preformed defence mechanisms, activation of plant defence signalling, accumulation of reactive oxygen species and initiation of hypersensitive response (HR) in some cases (Kamoun et al 1999;Heath 2000;Lauge et al 2000;Mellersh et al 2002;Mellersh and Heath 2003;Christopher-Kozjan and Heath 2003;Shimizu et al 2003;Mysore and Ryu 2004). Some essential nonhost resistance genes have recently been cloned from Arabidopsis.…”
Section: Introductionmentioning
confidence: 99%